Interactions between magnetic resonance imaging and dental material - Chalakuzhiyl Abraham Mathew; Sudhakara Maller; Maheshwaran (Wolters Kluwer Medknow Publications, 2013)
Magnetic resonance imaging (MRI) has become a common and important life-saving diagnostic tool in recent times, for diseases of the head and neck region. Dentists should be aware of the interactions of various restorative dental materials and different technical factors put to use by an MRI scanning machine. Specific knowledge about these impacts, at the dentist level and at the level of the personnel at the MRI centers can save valuable time for the patient and prevent errors in MRI images. Artifacts from metal restorations are a major hindrance at such times, as they result in disappearance or distortion of the image and loss of important information.